2017
DOI: 10.1177/0379572117720012
|View full text |Cite
|
Sign up to set email alerts
|

Societal Costs of Micronutrient Deficiencies in 6- to 59-month-old Children in Pakistan

Abstract: Background: In Pakistan, nearly half of children younger than 5 years are stunted, and 1 in 3 is underweight. Micronutrient deficiencies, a less visible form of undernutrition, are also endemic. They may lead to increased morbidity and mortality as well as to impaired cognitive and physical development. Objective: To estimate the lifetime costs of micronutrient deficiencies in Pakistani children aged between 6 and 59 months. Methods: We develop a health economic model of the lifetime health and cost consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…A deficiência de micronutrientes tem se mostrado como um importante desafio para a saúde pública, especialmente em países em desenvolvimento e subdesenvolvidos (Bhutta et al, 2013). O custo da deficiência de micronutrientes em crianças de 6 a 59 meses foi avaliado no Paquistão, sob a perspectiva da sociedade, e foi estimado um total de 46 milhões de dólares em gastos médicos e de 3.222 milhões de dólares em perda de produtividade, representando cerca de 1,5% do produto interno bruto do país (Wieser et al, 2017). Uma avaliação similar foi conduzida nas Filipinas e foi estimado um custo total de 30,3 milhões de dólares com gastos médicos e de 618,2 milhões de dólares com perda de produtividade (Wieser et al, 2013).…”
Section: Discussionunclassified
“…A deficiência de micronutrientes tem se mostrado como um importante desafio para a saúde pública, especialmente em países em desenvolvimento e subdesenvolvidos (Bhutta et al, 2013). O custo da deficiência de micronutrientes em crianças de 6 a 59 meses foi avaliado no Paquistão, sob a perspectiva da sociedade, e foi estimado um total de 46 milhões de dólares em gastos médicos e de 3.222 milhões de dólares em perda de produtividade, representando cerca de 1,5% do produto interno bruto do país (Wieser et al, 2017). Uma avaliação similar foi conduzida nas Filipinas e foi estimado um custo total de 30,3 milhões de dólares com gastos médicos e de 618,2 milhões de dólares com perda de produtividade (Wieser et al, 2013).…”
Section: Discussionunclassified
“…We estimated the cost-effectiveness of price subsidies on FPCF for the reduction of iodine, iron and vitamin A deficiencies in 6–23-month-old Pakistani children. For this purpose, we adapted a previous model of the societal costs of micronutrient deficiencies in Pakistan ( 17 ) to the districts of Faisalabad and Hyderabad, and carried out a survey including a hypothetical marketing experiment among 1764 households. We then estimated the net cost per DALY averted of different price subsidies covering different socio-economic strata.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the current lifetime costs of IoD, IDA and VAD in a birth cohort of children affected by these deficiencies between the ages of 6 and 23 months. These costs were calculated by adapting the model of the societal costs of MND in Pakistan ( 17 ) to the districts of Faisalabad and Hyderabad ( 19 ) . The health and costs consequences of MND in this age group are described in detail in the online supplementary material (Section 1, Tables S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
“…A study focusing on estimates of disability-adjusted life years and their monetization showed that short-term economic costs of micronutrient malnutrition in India amounted to 0.8% to 2.5% of the gross domestic product [14]. The health and cost consequences of iodine, iron, vitamin A, and zinc deficiencies were assessed in Pakistani children: Societal costs amounted to 1.44% of gross domestic product and 4.45% of disability-adjusted life-years in Pakistan in 2013, which hindered the country’s development [111].…”
Section: Micronutrient Unavailability As Cause Of Deficiencymentioning
confidence: 99%